IL-2Rα KO mice exhibit maternal microchimerism and reveal nuclear localization of IL-2Rα in lymphoid and non-lymphoid cells - Wong, Victoria A.; Dinh, Kristie N.; Chen, Guangchun; Wrenshall, Lucile E. (Frontiers in Immunology, 2024)
Introduction IL-2Rα knock out (KO) mice have been instrumental to discovering the immunoregulatory properties of IL-2Rα. While initially thought of only as a stimulatory cytokine, IL-2 and IL-2Rα KO mice revealed that this cytokine-receptor system controls immune responses through restimulation-induced cell death and by promoting the survival of T regulatory cells. Although described mostly in the context of lymphocytes, recent studies by our laboratory showed that IL-2R is expressed in smooth muscle cells. Given this finding, we sought to use IL-2Rα KO to determine the function of this receptor in vascular smooth muscle cells. Surprisingly, we found that IL-2Rα KO vascular smooth muscle cells had detectable IL-2Rα. Methods We used multiple gene and protein-based methods to determine why IL-2Rα KO vascular smooth muscle cells exhibited IL-2Rα protein. These methods included: genomic sequencing, assessing cells and tissues for evidence of maternal microchimerism, and determining the half-life of IL-2Rα protein. Results Our studies demonstrated the following: (1) in addition to the cell surface, IL-2Rα is localized to the nucleus; (2) the genetic deletion of IL-2Rα is intact in IL-2Rα KO mice; (3) both IL-2Rα KO and WT tissues show evidence of maternal microchimerism, the likely source of IL-2Rα (4) IL-2Rα is transmitted between cells; (5) IL-2Rα has a long half-life; and (6) nuclear IL-2Rα contributes to the regulation of cell proliferation and size. Conclusion Our findings suggest that the phenotype of complete IL-2Rα loss is more severe than demonstrated by IL-2Rα KO mice, and that IL-2Rα plays a here-to-fore unrecognized role in regulating cell proliferation in non-lymphoid cells.